2021
DOI: 10.1002/adfm.202101297
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Bottom‐up Synthesis of Ultrasmall CuS Nanodots in Cancer Cells for Simultaneous Photothermal Therapy and COX‐2 Inactivation

Abstract: The clinical application of photothermal therapy (PTT) is limited by the accuracy of thermal damage and the risk of tumor metastasis and relapse induced by hyperthermia‐related inflammation. Intracellular bottom‐up synthesis (iBuS) of CuS nanoparticles from small‐molecule precursors inside tumor cells triggered by tumor specific stimuli is a promising strategy to enhance the precision of PTT treatment and reduce the risk of nondegradable metal nanoparticles. Herein, monolocking nanoparticles (MLNPs) with Cu‐me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 46 publications
(60 reference statements)
0
33
0
Order By: Relevance
“…Various nanoplatforms have been designed to realize multi-modal synergistic therapy, [7][8][9][10] among which dual-modal synergistic therapy, such as chemotherapy/PTT, chemotherapy/CDT and CDT/PTT, has been wildly reported, while synergistic tri-modal synergistic therapy, such as chemotherapy/CDT/PTT, is still at an early age due to the difficulty in designing a more complex system. Two-dimensional (2D) nanomaterials, such as graphene, 11-14 metal oxides and transitional metal chalcogenides, [15][16][17][18][19] have attracted much attention in biological applications due to their unique optical properties and excellent biocompatibility. Specifically, palladium nanosheets (Pd NSs), as typical 2D materials, exhibit several unique characteristics, such as strong near-infrared (NIR) light absorption and high photothermal conversion efficiency, which have potential applications in photothermal therapy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various nanoplatforms have been designed to realize multi-modal synergistic therapy, [7][8][9][10] among which dual-modal synergistic therapy, such as chemotherapy/PTT, chemotherapy/CDT and CDT/PTT, has been wildly reported, while synergistic tri-modal synergistic therapy, such as chemotherapy/CDT/PTT, is still at an early age due to the difficulty in designing a more complex system. Two-dimensional (2D) nanomaterials, such as graphene, 11-14 metal oxides and transitional metal chalcogenides, [15][16][17][18][19] have attracted much attention in biological applications due to their unique optical properties and excellent biocompatibility. Specifically, palladium nanosheets (Pd NSs), as typical 2D materials, exhibit several unique characteristics, such as strong near-infrared (NIR) light absorption and high photothermal conversion efficiency, which have potential applications in photothermal therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Two-dimensional (2D) nanomaterials, such as graphene, 11–14 metal oxides and transitional metal chalcogenides, 15–19 have attracted much attention in biological applications due to their unique optical properties and excellent biocompatibility. Specifically, palladium nanosheets (Pd NSs), as typical 2D materials, exhibit several unique characteristics, such as strong near-infrared (NIR) light absorption and high photothermal conversion efficiency, which have potential applications in photothermal therapy.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16] Several studies have demonstrated the superiority of H 2 S as an internal stimulus for drug delivery. [17][18][19][20][21][22][23][24][25][26][27][28] For instance, copper sulfide (CuS) formation via the reaction between H 2 S and copper ions was utilized to release copper-coordinated doxorubicin (DOX) from protein nanocages. [29] In situ formation of CuS was used for activating photothermal therapy and triggering drug release from liposomes [30] or metal-organic framework.…”
Section: Introductionmentioning
confidence: 99%
“…In this general theme, the design of nanoparticles is an extremely developed research activity, in order to satisfy numerous applications [4] [5]. The field of use of nanoparticles seems unlimited, from nanomedicine [6] [7] to agriculture elaboration protocols have evolved a lot within the classical top-down [14] [15] or bottom-up approaches [16] [17]. Currently, processes are moving towards more eco-friendly approaches [18] [19] that can be part of sustainable development [20] [21].…”
Section: Introductionmentioning
confidence: 99%